Answer:
x = 9
TH = 12
Step-by-step explanation:
since TM is half of HM, the equation is:
2(21 - x) = 3x - 3
42 - 2x = 3x - 3
45 = 5x
x = 9
TH = 21 - x
TH = 21 - 9
TH = 12
2/3 times x-4 = 6
thats the answer :)
Your answer is C. 500,000
Answer:
12 * Answer:
12 x 3 = 36 + 6 = 42,
Step-by-step explanation:
Step-by-step explanation:
Let Susan's present age be x
Now, after 7 years ( her age will become 7 +x then) she'll be 2 as old she was 3 years ago.
Her age 3 years ago must be x-3
Now according to question,
twice Her age 3 years ago = her age after 7 years
now,
2(x-3) = 7+x
2x-6 = 7+x
2x-x =7+6
x = 13
x = 13
Therefore, her age presenr age is 13 years.